Financial Literacy and QRIS Adoption as Determinants of MSME Financial Performance in Binjai City - Devi Purnama Sari; Sri Hartati Sidauruk; Muhammad Saleh Rizkian (Information Technology and Science (ITScience), 2026)
This study aims to analyze the influence of financial literacy and the adoption of the Quick Response Code Indonesian Standard (QRIS) on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in the culinary district of Binjai City. The study employs a quantitative approach with an associative research design. The research population consists of all MSME operators in the Binjai City culinary district who have been in business for at least one year and utilize QRIS as a payment method. Purposive sampling was used to select a sample of 80 respondents. Primary data were collected through the distribution of questionnaires. Data analysis was conducted using multiple linear regression with the aid of IBM SPSS Statistics 26 software. The results indicate that financial literacy has a positive and significant effect on MSME financial performance, evidenced by a calculated t-value of 6.162 (exceeding the t-table value of 1.991) and a significance level of 0.000 (< 0.05). Furthermore, QRIS adoption also positively and significantly influences MSME financial performance, with a calculated t-value of 4.522 (exceeding the t-table value of 1.991) and a significance level of 0.025 (< 0.05). These findings demonstrate that higher levels of financial literacy and more optimal QRIS implementation lead to improved financial performance for MSMEs in the Binjai City culinary district.